(3cJGH aj HjGf eWGdH YLjHIs
(3ChdgG (B:s
(3gPg eSCdI ai bhe jMJLhf HGdbOQ hjbhdhf bO bVi GdCeQ hjMJLhf Hbhdg JYGdi (B:" (3Ef GdPjf SHbJ dge efG GdMSfi ChdFc YfgG eHYOhf s
(3BNQgG (B:s
(3Je GdLhGH HYhf Gdedc GdhgGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdJGSY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3GdEeHQhRjGfG (B(404 d) s
Keywords: (3GdJhMjO hGdedd hGdfMds